Investigation of a jointed friction oscillator using the multiharmonic balance method - Süß, Dominik; Willner, Kai (Mechanical Systems and Signal Processing, 2014)
This paper covers the investigation of a nonlinear jointed structure in the frequency domain. Due to frictional nonlinearities the behavior of that system is approximated using the Multiharmonic Balance Method (MHBM). Two models of different complexity are presented. The first is a simple three degree-of-freedom model which is valid because of the special design of the structure. This model enables a very fast and accurate prediction of the stationary behavior of the real system. In order to attain a more general way of modeling structures including joints, the second model is a Finite Element (FE) model. For the discretization of the contact plane, “Zero Thickness” (ZT) elements are implemented. These elements allow the application of nearly arbitrary constitutive laws for describing the dynamic joint behavior. Here a coupled three dimensional contact law including dry friction effects is applied and the needed partial derivatives for the MHBM procedure are given analytically. Using measurements from the real structure and performing a model updating process, the parameters of the two presented models are estimated. The calculation results are compared to measurements in the frequency as well as in the time domain.
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-TM.invest_3
Keywords: Structural dynamics; Bolted joint; Multiharmonic Balance; FEM; Contact element